The typewriter mind: modernism, populism and anti-humanism. Issue 9 (1st September 2020) - Mead, Henry
ABSTRACT: Recent commentaries on the resurgence of populist nationalism have referred back to the early twentieth century. Such analogies are criticised by scholarly historians, but in a frame of post-humanist theory, the very method of comparison recalls early modernist treatments of political and historical language as essentially metaphoric and fictive. The essay focuses on T.E. Hulme's writing, drawing attention to three challenges to humanism described in his work. Firstly, it examines his critique of excessive scientific confidence that led to a 'nightmare of determinism'. Secondly, it shows how Hulme was both fascinated and disturbed by forms of vitalism that gave individuals agency but seemingly also a vulnerability to manipulation. Thirdly, Hulme advocates a form of a politics subordinated to a transcendent deity, again in reaction to humanist ideals. Through analysis of Hulme's essays on crowd psychology, historical prejudice, and the political use of metaphor, the essay tests parallels between political narratives in the 1910s and the present day, and considers the constructive ends to which Hulme's problematic worldview could be put.